EFEKTIVITAS PRAPERADILAN DAN KEBERADAAN HAKIM KOMISARIS DALAM SISTEM PERADILAN PIDANA INDONESIA - Johansyah, Johansyah (Faculty of Law, University of Palembang, 2020)
The judge commissioner has a supervisory function at the initial examination stage which includes arrest; search; confiscation and examination of documents has been carried out legally or not. Judge Commissioner is to better protect human rights guarantees in the criminal process and avoid traffic jams by the arising of discrepancies between investigating officers from different agencies. The existence of a commissioner judge in the Indonesian criminal justice system which has very broad authority can make it difficult / hinder the operation of the criminal justice system. So that the existence of pretrial institutions is considered to be able to accommodate the protection of human rights of suspects in criminal offenses, as mandated by the International Covenant on Civil and Political Rights (ICCPR).